Penerapan E-Modul Berbasis Digital Flipbook Untuk Menanggulangi Penyalahgunaan Narkoba Dan Kenakalan Remaja Di Desa Bedahlawak - Iin Baroroh Maarif; Ulfa Wulan Agustina; Olifia Diajeng Ayu Mawarni; Ardip Subiyanto (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
At this time the development and association of the younger generation is very free. The development of technology and the era of free trade are supporting factors. In addition, the existence of social media makes everything easier to access and get. One of the negative impacts of this is the increase in juvenile delinquency, drug abuse and deviations committed by other teenagers. This community service activity is carried out by the academic community of KH University. A. wahab hasbullah aims to provide insight into knowledge for teenagers to always be vigilant and not fall into juvenile delinquency or drug abuse and others. The method used in this activity is socialization, as well as mentoring in the form of seminars for teenagers. The results of this activity help the younger generation to always be introspective and not fall into these negative things.